Private equity and the demise of the local the loss of community economic power and autonomy - Feldman, Maryann P. 1955-; Kenney, Martin (Cambridge elements. Elements in Reinventing Capitalism, 2024)
Capitalism is a powerful engine that requires finance. Private equity is part of the neoliberal transformation of capitalism that has failed the average citizen and unleashed a tsunami of leveraged acquisitions that have destroyed entire sectors of our economy. Private equity has become a powerful force that has moved from restructuring industrial firms to buying up just about any economic activity in local communities that has assets that can be monetized, without any consideration of the impact on the quality of life and well-being of the community. Th a process has been aided and abetted by government policy. The authors of this Element explain the workings of the private equity model and the reasons it has been so profitable. They document the effects of PE on firms and communities by examining a range of activities that once had a local focus. They conclude by offering policy recommendations